Mechanics of Additive and Advanced Manufacturing, Volume 9 Proceedings of the 2017 Annual Conference on Experimental and Applied Mechanics (Conference Proceedings of the Society for Experimental Mechanics Series,, 2018)
Mechanics of Additive and Advanced Manufacturing, Volume 9 of the Proceedings of the 2017 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the ninth volume of nine from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies, including: Design, Optimization Experiments Computations Materials for Advanced Manufacturing Processes (3D printing, micro- and nano-manufacturing, powder bed fusion, directed energy deposition, etc.) Mechanics Aspects of Advanced Manufacturing (e.g. mechanical properties, residual stress, deformation, failure, rate-dependent mechanical behavior, etc.).